THE EFFECT OF PRICES AND PROMOTIONS ON LUTI DRUM BUYING DECISION IN TANJUNG PINANG - Herri Sumantoro; Muhammad Imam Tabrani; Sabri (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
This study aims to test the effect of price and promotion on the purchasing decision of Luti Gendang in Tanjung Pinang. The repondents in this study are consumers in Tanjung Pinang. The number of respondents in this study was 100 respondents. Sampling is carried out by purposive sampling technique. This study used multiple linear regression analysis techniques with SPSS as an analysis tool. The results of multiple linear regression tests showed that: 1) The price partially had a significanteffect on the purchasing decision of Luti Gendang in Tanjung Pinang. 2) Promotion partially affects the purchase decision of Luti Gendang in Tanjung Pinan